Evaluation of lead poisoning in Opium Consumers in Mashhad, Iran, 2016Evaluation of Lead Poisoning in Opium Consumers - Najari, Fares; Alizadeh Ghamsari, Anahita; Vahabzadeh, Maryam; Abolbagaei, Seyed Mojtaba; Baradaran Kayal, Ideh; Najari, Dorsa (International Journal of Medical Toxicology and Forensic Medicine, 2018)
Background: Because opium is mixed with lead to increase its weight, the prevalence of lead poisoning is high among opium consumers. Hence, measurement of serum lead level in these people is important for the prevention or early treatment of lead poisoning. To evaluate the blood lead level in opium consumers. Methods: In this cross-sectional and descriptive study, a total of 214 opium consumers with lead poisoning referred to Imam Reza Hospital in Mashhad, Iran, in 2016, were evaluated. Atomic absorption spectrophotometry (Covanta Energy, GB) was used to measure the lead level of the blood samples. Results: The mean (SD) age of the participants was 43.11(18.14) year, also their average (SD) blood lead level was 139.5(48.5) µg/dL. No relationship was found between the blood lead level and age in the participants (P=0.11). The number of male participants was significantly higher than females in this study (92.5% vs. 7.5%). Also about 129(60.3%) participants consumed opium orally and 85(39.7%) ones used opium by inhalation. Conclusion: The blood lead level is higher than the acceptable limit in opium addicts, and the risk of lead poisoning should be considered among them, especially in oral consumers.